Development of an integrated pancreatic disease service. Issue 2 (9th January 2011) - Jupp, James A; Johnson, Colin D; Shek, Fanny W; Fine, David R
Abstract : An integrated pancreatic disease unit needs to deliver high-quality care both to patients with malignant and non-malignant pancreatic disease. The regionalisation of pancreatic cancer services which followed the publication of policy frameworks by the Department of Health and NHS executive led to the development of disease-site-specialised high-volume multidisciplinary teams. As the majority of patients with pancreatic cancer are not suitable for surgery, partner hospitals within a region need to provide access to a wide range of non-surgical treatment. The implementation of such working may require pooling of local resources to create networks of equivalence to tertiary centres. The provision of care to non-malignant pancreatic disease can benefit from this type of working and services can be modelled on, and integrate with, cancer services. One way of achieving this is to establish working groups based upon diseases rather than traditional departments, which can deliver standardised and optimal care with a patient-centred approach. However, this poses a number of potential problems. This review examines how an integrated pancreatic unit may be developed in district general and larger hospitals, and also describes our experience in developing such a unit.